Different Human Immune Lineage Compositions Are Generated in Non-Conditioned NBSGW Mice Depending on HSPC Source - Hess, Nicholas J.; Lindner, Payton N.; Vazquez, Jessica; Grindel, Samuel; Hudson, Amy W.; Stanic, Aleksandar K.; Ikeda, Akihiro; Hematti, Peiman; Gumperz, Jenny E. (Frontiers in Immunology, 2020)
NBSGW mice are highly immunodeficient and carry a hypomorphic mutation in the c-kit gene, providing a host environment that supports robust human hematopoietic expansion without pre-conditioning. These mice thus provide a model to investigate human hematopoietic engraftment in the absence of conditioning-associated damage. We compared transplantation of human CD34+ HSPCs purified from three different sources: umbilical cord blood, adult bone marrow and adult G-CSF mobilized peripheral blood. HSPCs from mobilized peripheral blood were significantly more efficient (as a function of starting HSPC dose) than either cord blood or bone marrow HSPCs at generating high levels of human chimerism in the murine blood and bone marrow by 12 weeks post-transplantation. While T cells do not develop in this model due to thymic atrophy, all three HSPC sources generated a human compartment that included B lymphocytic, myeloid, and granulocytic lineages. However, the proportions of these lineages varied significantly according to HSPC source. Mobilized blood HSPCs produced a strikingly higher proportion of granulocyte lineage cells (~35% as compared to ~5%), whereas bone marrow HSPC output was dominated by B lymphocytic cells, and cord blood HSPC output was enriched for myeloid lineages. Following transplantation, all three HSPC sources showed a shift in the CD34+ subset towards CD45RA+ progenitors along with a complete loss of the CD45RA-CD49f+ long-term HSC subpopulation, suggesting this model promotes mainly short-term HSC activity. Mice transplanted with cord blood HSPCs maintained a diversified human immune compartment for at least 36 weeks after the primary transplant, although mice given adult bone marrow HSPCs had lost diversity and contained only myeloid cells by this time point. Finally, to assess the impact of non-HSPCs on transplantation outcome, we also tested mice transplanted with total or T cell-depleted adult bone marrow mononuclear cells. Total bone marrow mononuclear cell transplants produced significantly lower human chimerism compared to purified HSPCs, and T-depletion rescued B cell levels but not other lineages. Together these results reveal marked differences in engraftment efficiency and lineage commitment according to HSPC source, and suggest that T cells and other non-HSPC populations affect lineage output even in the absence of conditioning-associated inflammation.